Preparation of Water Repellent Layer on Glass Using Hydrophobic Compound Modified Rice Hull Ash Silica - Alfa Akustia Widati; Nuryono Nuryono; Dessy Puspa Aryanti; Madjid Arie Wibowo; Eko Sri Kunarti; Indriana Kartini; Bambang Rusdiarso (Universitas Gadjah Mada, 2018)
In this study water repellent layered glass has been prepared by coating silica (SiO2) combined with a hydrophobic silane compound. SiO2 was extracted from rice hull ash and two silane compounds, namely hexadecyltrimethoxysilane (HDTMS) and trimethylchlorosilane (TMCS) were used. Coating was performed through two deposition techniques, i.e. one step (mono-layer) and layer by layer (LBL, multi-layer). The effect of silane to SiO2 mole ratio, silane type and layer number on the glass characters was evaluated. Characterization included hydrophobicity, transparency, surface roughness and stability of coating. Results showed that increasing the mole ratio of silane to SiO2 and the layer number increased the hydrophobicity of the glass surface. The optimum mole ratio was 5:1 and the significant increase of contact angle occurred at lower mole ratio, but the stability tends to be increased at higher mole ratio. For HDTMS-SiO2 layer, the technique of LBL technique produced a coating with higher hydrophobicity and transparency than single-stage one. The LBL technique produced the highest water contact angle of 103.7° with transmittance of 96%, while for TMCS-SiO2 layer the one stage technique produced hydrophobic layer with higher water contact angle of 108.0° and transparency about 94.52%. The prepared hydrophobic glasses were relatively stable in polar and non-polar solvents, but unstable to ambient conditions.